Adiponectin-derived pentapeptide ameliorates psoriasiform skin inflammation by suppressing IL-17 production in γδT cells. Issue 1 (April 2022) - Suh, Joong Heon; Lee, Yuri; Ohn, Jungyoon; Kim, Eun Ju; Kim, Tae-Gyun; Jo, Seong Jin; Kim, Sung Joon; Chung, Jin Ho
Abstract: Background: Psoriasis is a common immunologic chronic skin disease that affects at least 100 million individuals worldwide. Adiponectin is associated with psoriasis and suppresses psoriasiform inflammation. Recently, a small-sized transdermally deliverable 5-mer peptide (GLYYF; P5) was discovered as a potential adiponectin receptor 1 agonist. Objectives: To confirm reduction in adiponectin protein level in the human skin and investigate whether functional adiponectin replenishment by topical P5 application improves psoriasiform skin inflammation. Methods: Adiponectin protein expression in the skin of individuals with psoriasis and normal skin was examined by immunofluorescence staining. Imiquimod-induced psoriasis-like skin inflammation was induced in wild-type (WT) and adiponectin-deficient ( Adipoq −/− ) mice. Vehicle and P5 were topically applied to the back skin and ears of mice. Histological study, reverse-transcription quantitative polymerase chain reaction, multiplex-bead array assay, and flow cytometric analysis were performed. Results: Adiponectin protein expression was downregulated both in the epidermis and dermis of psoriatic lesions as compared to that in the normal skin. Topically applied P5 attenuated the severity of imiquimod-induced psoriatic dermatitis in both WT and Adipoq −/− mice by decreasing the expression of psoriasis-related cytokines ( Il17a, Il1b, Il6, and Tnfa ) . P5 application significantly reduced the proportion of interleukin-17A–producing γδT cells. Conclusion: Transdermally deliverable adiponectin receptor 1 agonist, P5, can be a potential peptide drug to manage psoriasis by mediating the anti-psoriatic effect of adiponectin Highlights: Adiponectin protein expression was lower in psoriasis lesion than in the normal skin. Topical application a transdermally deliverable AdipoR1 agonist 5-mer peptide, P5, improved psoriasiform dermatitis. Similar to the native adiponectin, P5 induced an anti-inflammatory effect by reducing IL-17A production from γδT cells. This study shows that the replenishment of adiponectin function by P5 can be a new anti-psoriatic treatment strategy.